Evaluation of blaGES-5 and bla veb-1 genes with multidrug-resistant extend, pandrug resistance patterns (MDR, XDR, PDR), and biofilm formation in Pseudomonas aeruginosa isolates - Ali, Fattma A.; Bakir, Sevan Hassan; Haji, Sayran Hamed; Hussen, Bashdar M. (Cellular and Molecular Biology, 2021)
Pseudomonas aeruginosa is a ubiquitous microorganism that is difficult to treat due to the increasing prevalence of multidrug resistance patterns. A total of 227 samples were taken from different clinical samples during the study period from January 2018 to December 2018. The isolates were identified with antibiotic sensitivity testing with ESBL by the Vitek-2 automated method. MDR, XDR, and PDR were determined. 40 (17.6%) isolates were positive for P. aeruginosa, maximum of ESBL and MBL. Positive isolates were detected in the burn, coexisting ESBL + MBL enzymes in 21 (52.5%) of our isolates. Imipenem followed by Meropenem were found to be effective against ESBL and MBL producers. Resistance was reached between 72-100% to 5 antibiotics. The frequency of PDR, MDR, and XDR were 5%, 50%, and 45%, respectively. The frequency of co-production between MDR, XDR, and PDR with MBL, ESBL, and Biofilm was 35%, 12.5% and 5%, respectively. Among the ESBLs, the frequency of distribution of bla VEB-1gene and blaGES-5 gene was 50% and 40 %, respectively. Bacterial isolates simultaneously carrying blaVEB-1 gene with multiple β-lactamases of different classes of biofilm, MDR, PDR, and XDR as same as a coexisting blaGES-5 gene. One isolate was detected as new isolates registered in global gene bank as locally P. aeruginosa isolates in Erbil city (LOCUS MN900953). The phylogenetic trees of the blaVEB gene isolates were demonstrated a genotype closely related to others, deposited in GenBank similar to the P. aeruginosa gene; gene sequencing revealed a 99% similarity with other isolates deposited in GenBank.